Open architecture pc-based CNC controller - Yusoff, Wan Azhar (2006)
The objectives of this project are two: developing CNC controller and developing a prototype machine to implement the controller. The developed CNC controller is an Open Architecture PC based type controller. Besides having all normal controller functions, the developed controller also permit upgradeable and interchangeable controller functions. Because of the open architecture characteristic, different interpolator algorithms are able to be executed for different manufacturing applications. Furthermore, the controller function is located inside a PC. The prototype machine is a general purpose three-axis machine flexible enough to execute different manufacturing processes ranging from pen-plotting, sheet metal processing and engraving applications just by changing the tool application. The CNC controller and the ·prototype machine is successfully developed, integrated and tested for two types of applications: wood engraving and penplotting. The result is that the developed machine is capable of tracing any 2D drawing, letters and Arabic scripts. As a testing application, custom wood engraving application was carried out and sold to the public with positive feedback. By having the controller and the prototype machine, KUKTEM now has platform to further research into CNC technology. With the knowledge of the CNC controller, CNC machines can be locally engineered thus reducing future imports of CNC machines.